(untitled) (PROCEEDINGS OF THE NATIONAL ACADEMY OF SCIENCES OF THE KYRGYZ REPUBLIC, 2025)
Archaeological monuments are the basis of cultural heritage, and proper use of their tourism potential will contribute to the development of the country’s economy and cultural sector. They are a unique tourism resource and can make a significant contribution to the economic and cultural development of the country. The rich historical heritage of Kyrgyzstan is one of the main factors attracting tourists. However, for the effective use of these monuments it is necessary to study, preserve, restore and provide them with modern tourism infrastructure. In this work, ways to effectively use archaeological sites in tourism were analyzed. The successful experience of other countries was reviewed and modern methods were proposed. Apart from preserving the value of the monuments, proposals are being made to develop infrastructure, use information technology and ensure participation of local people to attract tourists. In addition, strategies for effective use of location, historical significance and aesthetic features of the monuments were studied. These events are aimed at increasing the country’s tourism potential and passing on cultural heritage to future generations.